Evaluación de la normativa legal turística ecuatoriana para la generación de espacios de turismo rural en la provincia de Manabí - Navarrete Marquez, Renán Ignacio (2022)
The objective of this research is to evaluate the legal regulations of rural tourism in the province of Manabí for the development of proposals that allow the generation of tourist spaces in said territory. Thus, for the development of the proposal, a methodology was established, consisting of three phases that responded to the specific objectives, such as: the characterization of the province of Manabí with emphasis on rural areas with tourism potential, which in the first phase The five selected cantons have potentialities identified in the matrix of characteristics and tourist potentialities, highlighting that they have spaces for the generation of opportunities; the evaluation of the current legal regulations for the development of rural tourism in Manabí, in the second phase the current legal regulations were evaluated, which allowed to evidence the most appropriate legal parts for the generation of rural tourism spaces; and finally to propose an ordinance model that allows the generation of rural tourism spaces in the province of Manabí, where criteria for the generation of opportunities were analyzed, being necessary to apply the criteria of experts to determine the structure of the proposal. In conclusion, it was determined that the ordinance model would be composed of six macro strategies, seven actions, six ordinances and five principles and strategies in the four elements of sustainability and that the areas have potentialities of greater magnitude for the use of rural tourism.